Effect of steel fiber-volume fraction and distribution on flexural behavior of Ultra-high performance fiber reinforced concrete by digital image correlation technique. (21st February 2022) - Meng, Shaoqiang; Jiao, Chujie; Ouyang, Xiaowei; Niu, Yanfei; Fu, Jiyang
Highlights: The fibers number per unit area for S0.5, S1.0, S1.5, and S2.0 were 7, 14, 21, and 31, respectively. The fiber pull-out length in cracked zone with different fiber-volume fractions was about 3.56 mm. The fiber orientation factor (ηθ ) of S0.5, S1.0, S1.5, and S2.0 were 0.80, 0.79, 0.69 and 0.61 respectively. A linear relationship between fiber pull-out number and equivalent bending stress, as well as between total fiber pull-out length and toughness, was established. A quadratic relationship between the ηθ and the fiber pull-out number is proposed. The flexural-tensile strength ratio (β) is about 2.52 for UHPFRC exhibiting deflection hardening behavior. The tri-linear softening curve analysis exhibited good agreement with the experimental results. Abstract: This paper investigated the effect of steel fiber-volume fraction (0.5%, 1.0%, 1.5%, and 2.0%) and distribution on the flexural behavior of ultra-high performance fiber reinforced concrete (UHPFRC). Digital image correlation (DIC) was used to obtain the crack propagation behavior of UHPFRC under bending load. With increasing fiber-volume fraction, the crack-propagation path becomes more zigzagged. Based on the flexural response of UHPFRC and fiber distribution on the crack plane, a correlation between fiber distribution characteristics and flexural behavior was discussed. The fibers number per unit area for S0.5, S1.0, S1.5, and S2.0 were 7, 14, 21, and 31, respectively. The fiber pull-out length in cracked zone with different fiber-volume fractions was about 3.56 mm. The fiber orientation factor (ηθ ) of S0.5, S1.0, S1.5, and S2.0 were 0.80, 0.79, 0.69 and 0.61 respectively. A quadratic relationship between the ηθ and the fiber pull-out number is proposed. The flexural-tensile strength ratio (β) is about 2.52 for UHPFRC exhibiting deflection hardening behavior. Finally, the post-cracking tensile behavior of UHPFRC was analyzed based on the matrix softening and fiber bridging curve models by the inverse analysis method. The tension softening curves obtained from the tri-linear softening curve analysis exhibited good agreement with the experimental results.